Exploring the Linkage between Temperature and Economic Growth in Bangladesh: An ARDL Approach - Uddin, S. M. Nasir; Islam, Ashraful; Howlader, Shazib (Indonesian Journal Publisher, 2024)
This study is investigated the nexus between temperature and GDP in Bangladesh and how GDP is affected by carbon emission, rainfall and temperature. The ARDL bound test is employed to examine the cointegration relationship among the variables and findings suggest that variables are cointegrated in both cases of dependent variable temperature and dependent variable of GDP. Results mirror that economic growth affect negatively the temperature and statistically significant for short run and long run. On the other hand, carbon emission and rainfall have statistically significant short run positive impact on GDP growth. The ECM result indicates the equilibrium converges to steady state at 78% annually when dependent variable is temperature and equilibrium also converges to steady state at 0.0891% annually, when dependent variable is GDP. Granger Causality test finds a one-way causal relationship between GDP and carbon emissions in both situation of the different dependent variables. Aftermath, results would say that carbon emission and rainfall have short run salutary impact on economic growth and the economic growth is conducive to reduce temperature in Bangladesh that moves to sustainable development. It might address underlying economic transitions such as shifts to greener industries or government interventions that promote sustainability. It will help researcher and policymakers for further study to identify environmental friendly growth projects that lead to reduce temperature in Bangladesh.